Hakikat Peserta Didik Dalam Pendidikan Islam - Sasmita Chairuna, Uli Ramadani Siagian, Zulkifli Dalimunthe, Robby Ardhana (ALACRITY : Journal of Education, 2023)
Writing this article aims to find out how the nature of students in Islamic education. One important component in an educational process is students. Adab which defines students as people who are studying or studying in educational institutions, and are called students, santri to students. This study uses a qualitative research method that is library research which uses books and other literature as the main object, and uses a descriptive method in analyzing the data. This descriptive analysis method provides clear, objective and systematic descriptions and explanations. This research found that every student must take part in a particular type of education or system to grow and develop himself. Learners are people who are in a phase of growth and development both physically and psychologically who need guidance from an educator. Students in searching for life values, must get full guidance from educators. According to Islamic education, children are born in a state of fitrah and the natural surroundings will give color to the value of their life, and determine how their condition will be in the future.